Daya Pacu Mikroba Pelarut Fosfat dan Penambat Nitrogen pada Tanaman Jagung - Latupapua, H.J.D.; Suliasih, Suliasih (Perhimpunan Biologi Indonesia, 2001)
ABSTRACTThe Stimulating Capacities of the Phosphate Solubilizing and the Nitrogen Fixing Microbes on the Maize Plant. The green house experiment has been carried out to study the effectiveness of the phosphate solubilizing microbes (PSM) and nitrogen fixing bacteria (NFB) on the growth of maize (Zea mays). The phosphate solubilizing microbes were Aspergillus sp. and Gigaspora margarita while the nitrogen fixing bacteria were Azospirillum sp. and Azotobacter sp. have been used in this experiment. The aim of the experiment was to find the suitable and effective inoculant on the maize and its expected the growth of the plant. The experiment used The Completely Randomize Design with three replicates. The treatments were uninoculated plant (control), the plants inoculated with single microbe of PSM, NFB and the combination of both. The results indicated that the phosphate solubilizing microbes (PSM) and the nitrogen fixing bacteria (NFB) which were either used in single or combination formula could stimulate the plant growth. The dual inoculation of Azotobacter sp. and Aspergillus sp. were found the higest yield of maize.Key words : The phosphate solubilizing microbes, the nitrogen fixing bacteria, Mycorrhiza vesicular arbuscular, Zea mays.